(untitled) (MedS Alliance Journal of Medicine and Medical Sciences, 2022)
INTRODUCTION: Menstrual Hygiene Management (MHM) for girls has long been a neglected issue in low income countries however there is increasing recognition that it should be included in research, programming, education and health policies. The aim of the study was to assess the menstrual hygiene management among adolescent school girls residing Inaruwa Municipality of Sunsari district. MATERIALS AND METHODS: A descriptive cross-sectional study design was conducted on 211 respondents and self-administered questionnaire used as data collection tool. Epi-data version 3.1 and SPSS version IBM 22 was used for data entry and analysis software respectively RESULTS: Majority 74.4% had their first menstruation at the age between 13-15years. In the first menstrual period, the girls were frightened (40.3%) and confused (36%). Entire girls revealed that they were using any type of absorptive materials during menstrual period. Nearly three-fifth of the girls (55.5%) only used sanitary napkin/pad as a protective material during menstruation and 14.2 percent of the girls were using old piece of cloth. Half of the girls (50.9%) used to change their absorptive materials twice a day and 32.5 percent of them changed thirst a day during their menstrual period. After the used of absorptive material, nearly two-third of the girls reported that they used to bury absorptive materials in separate place secretly, while 37.3 percent of girls reported that they used to burn. CONCLUSIONS: The menstrual hygiene practices at home seem to be satisfactory. However, in school, the insufficient toilets, dustbins were the reasons for making the menstruation hygiene difficult and impossible during the school hours. This lead to missing of classes, and school absenteeism during the periods.